Phosphodiesterase inhibitor pentoxifylline: An antiinflammatory/immunomodulatory drug potentially useful in some rheumatic diseases (1995)
Phosphodiesterase inhibitor pentoxifylline: an antiinflammatory/immunomodulatory drug potentially useful in some rheumatic diseases: Adjuvants, Immunologic/therapeutic use, Animals, Anti-Inflammatory Agents, Non-Steroidal/therapeutic use, Arthritis, Rheumatoid/drug therapy in Humans